LACK OF NOTIFICATION OF COMPULSORY NOTIFICATION DISEASES IN HOSPITAL SETTINGS - Rubens Griep (Universidade Federal de Goias, 2004)
This research encompasses the diseases of compulsory lack of notification inhospital settings and its interface with the Health Information System (Sistema de Informaçãode Saúde SIS) developed and implemented by the Welfare System in Brazil (Sistema Únicode Saúde SUS). It tries to identify the elements epidemiology is based on, referring to itsaspects as basis for the development of epidemiologic monitoring actions of contagiousdiseases in the country. It focuses on the following question: what are the factors thatcontribute and/or determine the flaws in the process of notification for compulsory notificationdiseases? The results obtained through a questionnaire presented to the personnel responsiblefor the Hospital Infection Control Service (Serviço de Controle de Infecção Hospitalar) showtheir lack of preparedness and technical knowledge, as well as their teams, in relation to thedynamic functioning of the Epidemiologic Vigilance Service (Serviço de VigilânciaEpidemiológica). It points to the flaws due to the influence exerted by the public and/or privatecharacter of the institutions and considers the possibility of lack of commitment and responsibility of the multi-professional team in the maintenance of the preestablished flow. As aproposal, we present an adoption of continuous educational actions through the implementationof a Long Distance Post Graduation course, aiming for the development of new possibilities forthe teaching-learning process, characterized by the ongoing quest for new knowledge and focuson the student. The implementation of a local and municipal Permanent Habilitation Programmay complement the need for updating, as well as make the discussion of the cases and dataof the reality possible, thus aiming to adopt joined measures in order to cope with the presentedepidemiologic situations.